The Roll-out of Child-friendly Fixed-dose Combination TB Formulations in High-TB-Burden Countries: A Case Study of STEP-TB - Lena Faust; Kawsar Abdi; Kristin Davis; Chen He; Caitlin Mehrotra; Emilie Stibolt (Journal of Epidemiology and Global Health, 2019)
Childhood tuberculosis (TB) has hitherto been treated through estimation of pediatric doses through the crushing of adult pills, but the bitter taste of the pills and the inaccuracy of this dosing method presents a challenge for both patients and healthcare providers, leading to poor treatment outcomes. The TB Alliance therefore launched the Speeding Treatments to End Pediatric-Tuberculosis (STEP-TB) project to incentivize the introduction of pediatric Fixed-Dose Combinations (FDCs) of TB drugs. This case study describes the elements of this project, evaluates its impact, and highlights future challenges for pediatric TB treatment. The impact assessment incorporates both market impact as well as projected public health impact, evaluating the availability, affordability, and quality of the FDCs, and lastly providing a projection of lives saved as a result of scale-up of the FDCs to near-universal availability and utilization, based on a publicly available pediatric TB-specific model. STEP-TB resulted in the development of two child-friendly FDCs that were successfully brought to market and made available in 20 of the project’s 22 high-burden countries. On the basis of a country-specific projection of pediatric TB mortality in Kenya, scale-up to near-universal availability and utilization of the new FDCs could reduce pediatric TB-associated mortality by 2660 cases over the next 5 years. Future challenges include maintaining affordable prices for the FDCs and considering mechanisms to incentivize their introduction among high-risk groups in low-burden countries.